Synthesize dual goals: A study on China’s ecological poverty alleviation system - Ming LEI; Xuan-yu YUAN; Xin-yan YAO (Journal of Integrative Agriculture, 2021)
How to break the vicious cycle of poverty and ecological degradation is widely concerned and discussed. In the poverty alleviation practices in China, ecological poverty alleviation (EPA) is regarded as an important way to synthesize the dual goals of poverty reduction and environmental protection and to achieve the win-win outcomes. Many Chinese researchers have fruitful research achievements on EPA yet they do not recognize that EPA is not a simple combination of various policies, but a complex system involving multiple policy instruments, governmental agencies, social forces, and agents. However, few studies abroad illustrate EPA in detail. They focus more on specific components of EPA such as payment for ecosystem services while overlooking the integral concept of EPA and practices from China. Based on field research in Guizhou Province, China, this paper proposes a framework of EPA with an effective multi-agent and co-government system, for demonstrating the concept and practice of EPA. With case analysis, we illustrate key elements in this system and their relationships, and how they play a vital role in pursuing win-win outcomes in environmental protection and poverty alleviation. The three dimensions of this EPA system have been discussed. The first is to strengthen the interaction among the agents. Many efforts should be made for establishing an efficient communication routine and a stable relationship among their interests. The second is to reinforce the connection between diverse elements in each policy subsystem, such as the systematization and coordination of the ecological industry development, the systematization of the links before, during, and after the relocation of ecological immigrants, etc. The third is to promote the interactions between the three subsystems, so that ecological enhancement, ecological compensation, and industrial development, and migration and relocation can promote each other, and ultimately promote the coordination of poverty alleviation and ecological protection in poverty-stricken areas. Thus, this paper analyzes how to establish the communication routine among the relevant agents of EPA, the interaction among the internal elements of the subsystems, and the relationship between the subsystems in series, trying to reveal the basic operating mechanism of the system.